Oligoether/Zwitterion Diblock Copolymers: Synthesis and Application as Cathode-Coating Material for Li Batteries - Masahiro Yoshizawa-Fujita (Polymers, 2021)
Poly (ethylene oxide) (PEO) has been investigated as an ion-conductive matrix for several decades due to its excellent properties. However, further improvements are needed to enable a PEO-based ion-conductive matrix for practical applications. In order to develop novel solid polymer electrolytes based on zwitterions, we synthesized diblock copolymers (PPEGMA-b-SPBs) with oligoether and zwitterionic side-chains and evaluated their physico-chemical properties. PPEGMA-b-SPBs with various unit ratios were synthesized by RAFT polymerization. PPEGMA-b-SPBs with/without LiTFSA exhibited two distinct glass transition temperatures regardless of the unit ratio of PEGMA and SPB. AFM observations clearly revealed phase-separated structures. The ionic conductivity of PPEGMA-b-SPBs increased even at a high salt concentrations such as [EO]:[Li] = 6:1 and was over 10−5 S cm−1 at 25 °C. This tendency is unusual in a PEO matrix. The oxidation stability of PPEGMA-b-SPBs was about 5.0 V vs. Li/Li+, which is a higher value than that of PEO. The improvement of the electrochemical properties is attributed to the introduction of the SPB block into the block copolymers. PPEGMA-b-SPBs were evaluated as cathode-coating materials for Li batteries. The discharge capacity and coulombic efficiency of the cells employing the cathode (LiNi1/3Mn1/3Co1/3O2 (NMC)) coated with the block copolymers were much higher than those of the cell employing the pristine cathode at the 50th cycle in the cut-off voltage range of 3.0–4.6 V.